importance of war games in military training - Almqati, Musalat bin Safar bin Ali; Bin Marni, Nour Azam Al-Lil; Shehab, Ahmed Abdel Hakim Abdel Rahman (Journal of Humanities & Social Sciences, 2018)
This study aimed to identify the importance of military games in military training.To arrive to the results and recommendations, the researcher uses descriptive analytical method through observation, induction and the study of the most important references and articles which are published. The researcher hopes that this study will provide tangible results highlighting the importance of military games in military training. One of the most important results of this study is that there is a great interest in the war games by the major countries and full dependence on the results of the war they are waging, especially the United States of America, which established the centers for this game and devoted to it much amounts of money. Among the most important recommendations of this study is the need to include a special curriculum for military games within the curricula adopted by the military institutions in Islamic countries since these games play an effective role in training leaders especially in decision-making, another recommendation is the importance of establishing centers for military games in military colleges to take advantage of the potential of this means, especially In training and qualifying leaders and staff of all different levels.